Silencer - Hall, James W. (James Wilson), 1947- (New York : Minotaur Books, 2010)
After his father, Earl Hammond, is shot dead and two deviant contract killers kidnap a family heir, Thorn, it is up to Frisco Hammond and his brother's wife to solve the two crimes, which may possibly be connected.
edited hb 2015-06-16
Keywords: Family secrets -- Fiction; Thorn (Fictitious character) -- Fiction; Suspense fiction